Exploring Diseases through Magnetic Resonance Imaging - Arwa Ali Alahmadi; Elaf Mawad Alharbi; Omar Salem Almehmadi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Magnetic Resonance Imaging (MRI) has emerged as one of the most essential and advanced tools in the realm of medical imaging, making significant contributions to the diagnosis of a diverse array of diseases. This sophisticated technique is renowned for its capability to produce highly detailed images of soft tissues and internal organs without the need for ionizing radiation, thereby minimizing the associated risks of radiation exposure. The primary aim of this paper is to delve into the pivotal role that MRI plays in the detection and diagnosis of various medical conditions, through an analysis of existing studies and a comprehensive review of the pertinent literature. Additionally, the methodologies employed in relevant research will be discussed, along with an examination of the findings and their implications for clinical practice